Paradigma Pendidikan Islam dan Keprofesionalan Guru dalam Menjawab Tantangan Global - Mahsun Mahfud (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
Islamic education must be directed from paradigm that past oriented (middle age) to the future. Not just preserve advancement, but also pioneering progress. Feudal paradigm must been replaced by Islam education paradigm that innovative and democratic. Therefore, we need harmonious planning and mutual agreement, that Islamic education must oriented to student, have multicultural character, and global perspective. Education has to become liberation process, not social and cultural domestication. One important aspect is to manifesting teacher professionalism that identified from competence aspect, responsibility, honesty, discipline, and high dedication to guard student to their successfulness.Â Â